Penggunaan Akronim dalam Media Sosial Status Facebook Bakal Calon Presiden Tahun 2024 - Sari, Vina Yulia; Juita, Novia (Persona: Kajian Bahasa dan Sastra, 2024)
Abstract This article was written based on the results of research on the use of acronyms in the social media Facebook statuses. The choice of social media Facebook status as a data source was motivated by the large number of acronyms found on social media Facebook status, making it difficult for readers to understand them, such as the Facebook accounts of presidential candidates in 2024 which still use acronyms in party names, names of communities, institutions, other words. trends, activities and more. Therefore, the problem presented in this article specifically concerns the use and pattern of forming acronyms in the social media Facebook status of presidential candidates in 2024. The data processed is in the form of words or phrases contained in the Facebook status object of presidential candidates in 2024. The method used Data collection uses a descriptive method, namely research that is carried out without using numbers but is obtained in the form of descriptive data in the form of vocabulary, but the data is taken first by copying and pasting the data. The results obtained are words that are shortened into acronyms and patterns of acronym formation from the data. The results of this research can be used to enrich language knowledge and lecture materials, including in morphology courses.